Pengembangan Media Pembelajaran E-Modul pada Elemen Dasar Fashion Design di SMKN 1 Sooko Mojokerto - Airiza Aulia; Peppy Mayasari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
In the learning process in class X of SMK majoring in Fashion Design, there are Basic Elements of Fashion Design which cover various topics. One of the topics taught is about the parts and forms of clothing. The teaching method applied is appropriate, but there needs to be development of the learning media used, namely e-modules, to make it easier for educators and students during the teaching and learning process. For this study, the Research and Development method was used by applying the ADDIE model through a series of steps, namely analysis, design, development, implementation, and evaluation. These stages are carried out to collect information about user needs, followed by development activities to create products. The findings of this study indicate that the level of validity of the e-module based on the assessment of media experts, material experts, and language experts reached an average of 3.28, falling into the very valid category. The results of classical student learning on the use of e-modules as learning media got 93.3% and were categorized as very good. Student responses to the e-module learning media regarding parts and forms of clothing recorded a score of 79.8% which was also in the very good classification. Therefore, it can be concluded that the e-module on clothing parts and forms is very valid for use in teaching because it is able to optimize student learning outcomes.